Evaluación in vitro de aminoácidos lisina y metionina con y sin protección (2015)
ABSTRACT: With the purpose to evaluate the rumen protección of the synthetic amino acids (AA) lysine and methionine, an in vitro rumen fermentation was performed where the parameters of ruminal degradability, gas production and release of ammonia were determined compaaared with urea as the N source. The DM degradability and release of ammonia were much higher with urea compared with the AA which did not differ between protected and unprotected sloures of the two AA.